Serum pepsinogen levels can quantify the risk of development of metachronous gastric cancer after endoscopic resection. Issue 5 (5th May 2016) - Iguchi, Mikitaka; Kato, Jun; Yoshida, Takeichi; Yamamoto, Yasuhide; Nakachi, Kenichiro; Fukatsu, Kazuhiro; Mori, Yoshiyuki; Maeda, Yoshimasa; Moribata, Kosaku; Shingaki, Naoki; Niwa, Toru; Deguchi, Hisanobu; et al.
Abstract : We have previously reported that serum pepsinogen (PG) can quantify the level of gastric mucosal atrophy, and that H. pylori eradication reduces cancer development in subjects with mild atrophy identified by serum PG levels. The aim of this study was to elucidate the predictive ability of serum PG levels for the development of metachronous gastric cancer (MGC) after endoscopic resection (ER) of primary cancer in association with H. pylori eradication. A retrospective chart review was performed, and 330 patients who underwent ER for initial early gastric cancer were enrolled. Presence or absence of H. pylori, serum PG levels, and endoscopic atrophy at ER were evaluated. H. pylori eradication was performed at the patient's request after ER. The incidence of MGC in these patients was analyzed. Of 330 patients, 47 developed MGC. Endoscopic extensive atrophy was observed more frequently in patients with MGC ( p = 0.001). Although PG I or PG II alone did not significantly differ according to development of MGC, the proportion of PG I/II ≤ 3.0, which is one of the criteria of PG test‐positive, was significantly higher in patients with MGC (83 vs . 69%, p = 0.04). H. pylori eradication after ER did not affect MGC development ( p = 0.2). On multivariate analysis, serum PG I/II ratio ≤ 3.3 was significantly associated with the development of MGC (hazard ratio: 3.66, 95% confidence interval: 1.47–12.25, p = 0.004). The risk of MGC after ER could be quantitatively predicted by the PG I/II ratio regardless of H. pylori status. Abstract : What's New? Helicobacter pylori infection is a frequent cause of chronic gastritis, which in the presence of an aggressive inflammatory milieu progresses to gastric atrophy, intestinal metaplasia and cancer. For some patients, H. pylori eradication can reduce gastric cancer development, though whether this is true for metachronous gastric cancer (MGC) remains uncertain. In this study, H. pylori eradication was found to have no affect on MGC incidence following endoscopic resection, which inevitably leaves behind atrophied gastric mucosa, a possible source of cancer development. MGC development was predicted by serum pepsinogen I/II ratio, identified here as a marker of gastric atrophy.